Molecularly imprinted vs. reversed-phase extraction for the determination of zearalenone: a method development and critical comparison of sample clean-up efficiency achieved in an on-line coupled SPE chromatography system - Lhotská, Ivona; Gajdošová, Barbora; Solich, Petr; Šatínský, Dalibor (Analytical and bioanalytical chemistry, 2018)
Sample preparation prior to chromatographic separation plays an important role in the analytical process. To avoid time-consuming and manual handling sample-prep, automated on-line techniques such as on-line SPE-HPLC are therefore preferred. In this study, two different on-line extraction approaches for mycotoxin/endocrine disruptor zearalenone (ZEA) determination using either molecularly imprinted polymer (MIP) with selective cavities and binding sites for extraction or a reversed-phase sorbent C18 providing non-selective interactions have been developed, validated, and compared. The validation characteristics were compared and the two methods were evaluated as being almost equal in terms of linearity, repeatability, precision, and recovery. Recoveries were in the range of 99.0-100.1% and limits of detection were found the same for both methods (1.5 μg L-1). Method precision calculated for spiked beer samples was better for C18 sorbent (2.5 vs. 5.4% RSD). No significant differences in the selectivity of either extraction method were observed. The possible reasons and further details associated with this finding are discussed. Finally, both validated methods were applied for the determination of ZEA contamination in beer samples. Due to ZEA's native fluorescence, chromatographic separation with fluorimetric detection (λex = 270 nm and λem, = 458 nm) was selected. Graphical abstract Determination of zearalenone in beer using an on-line extraction chromatography system.
Keywords: Endocrine Disruptors; nesteroidní estrogeny; Mycotoxins; Solid Phase Extraction; Mycotoxin; pivo; Estrogens, Non-Steroidal; On-line extraction; Chromatography, Reverse-Phase; Zearalenone; On-line SPE chromatography; endokrinní disruptory; vysokoúčinná kapalinová chromatografie; Food Analysis; zearalenon; chromatografie s reverzní fází; mykotoxiny; Chromatography, High Pressure Liquid; limita detekce; analýza potravin; Beer; molekulový imprinting; extrakce na pevné fázi; Limit of Detection; Solid-phase extraction; Molecularly imprinted polymers; Molecular Imprinting